2019
DOI: 10.4103/jfmpc.jfmpc_448_18
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of need for limiting family after two children: A cross-sectional study from a Northern State of India

Abstract: Background:Success of a programme of free-choice participation, like Family Planning Programme, can be envisaged only when focus is on the needs of the people. Although India was the first country to introduce Family Planning Programme, total fertility rate of 2.1 has not yet been achieved, highlighting that the need of limiting family after two children is not yet felt by the people of India. Therefore, the study was undertaken to assess need for limiting family and permanent methods, and factors influencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Both nuclear and other family structures (50;30.7%) were strongly correlated with contraceptive use (14;30.4%). Participants who acknowledged the influence of extended family members reported reduced contraceptive use, likely due to cultural norms discouraging contraceptive use [43] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both nuclear and other family structures (50;30.7%) were strongly correlated with contraceptive use (14;30.4%). Participants who acknowledged the influence of extended family members reported reduced contraceptive use, likely due to cultural norms discouraging contraceptive use [43] .…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study conducted in Northern India revealed a higher preference for temporary methods for limiting family size than permanent methods. One-third of respondents used permanent methods whereas another one third used temporary methods [43] .…”
Section: Discussionmentioning
confidence: 99%